2021
DOI: 10.1063/5.0027562
|View full text |Cite
|
Sign up to set email alerts
|

Simulation study of a pulsed DBD with an electrode containing charge injector parts

Abstract: By using a multispecies fluid model, the tunability and controllability of plasma parameters such as distributions of electron density, electron energy, ion density, and electric field in a microdielectric barrier discharge (DBD) with a charge injector electrode and driven by negatively polarized nanosecond pulsed voltage superimposed on a positive DC bias voltage are investigated. To this end, the effects of changing features of pulsed voltage like pulse rise time (10–20 ns), pulse peak width (10–15 ns), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 40 publications
2
13
0
Order By: Relevance
“…With comparing the distribution of electron and ion, it is found out that ion distribution peak occurs close to cone tip while for the electron it appears far away → → from the electrode tip, nearly in the centre of discharge gap. In our previous work on argon plasma for this structure [35], we showed that, during each repetition period, both electron and ion density distribution peaks perform a reciprocating motion between the cone tip and the dielectric surface. The same type of reciprocating motion for peak densities of electron and ion has also been seen here for CH 4 plasma.…”
Section: Simulation Results and Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…With comparing the distribution of electron and ion, it is found out that ion distribution peak occurs close to cone tip while for the electron it appears far away → → from the electrode tip, nearly in the centre of discharge gap. In our previous work on argon plasma for this structure [35], we showed that, during each repetition period, both electron and ion density distribution peaks perform a reciprocating motion between the cone tip and the dielectric surface. The same type of reciprocating motion for peak densities of electron and ion has also been seen here for CH 4 plasma.…”
Section: Simulation Results and Discussionmentioning
confidence: 75%
“…It consists of two electrodes (grounded and powered) and a dielectric barrier layer with a dielectric constant of 3.0 that covers the upper electrode (grounded electrode). The bottom electrode (powered) is engraved to a periodic cone-shape sharp array, establishing charge injection phenomena [35]. The dielectric layer has a thickness of 0.5 mm and the distance between the tip of cones and surface of the dielectric layer is 0.5 mm.…”
Section: Description Of the Model And Structurementioning
confidence: 99%
See 1 more Smart Citation
“…[15][16][17] Recently, we have shown theoretically and computationally that dielectric barrier discharges with charge injection points have further practical benefits. [18,19] Following that, in this experimental study, we explore methane conversion in an AC-driven charge injector DBD and compare the results to the usual flat electrode DBD plasma. The sharp points on the electrodes of this specific DBD produce a high-rate secondary electron emission due to the high strength of the local electric field, which might eventually boost methane activation and energy efficiency of the process.…”
Section: Introductionmentioning
confidence: 99%
“…The use of nonthermal plasma technologies is an alternative route to tackle the barriers in CH4 <math altimg="urn:x-wiley:16128850:media:ppap202200086:ppap202200086-math-0003" wiley:location="equation/ppap202200086-math-0003.png" xmlns="http://www.w3.org/1998/Math/MathML"><mrow><mrow><msub><mi>CH</mi><mn>4</mn></msub></mrow></mrow></math> activation and conversion; as such plasma technology has recently generated increased interest for gas processing [ 5 ] . Among many procedures and sources to generate nonthermal plasmas, dielectric barrier discharge (DBD) in comparison to the other systems is useful because of considerably high specific power density, low gas consumption, and strong potential for upscaling [ 6 ] . DBDs can operate at atmospheric pressure, which is most suitable for practical applications [ 7 ] .…”
Section: Introductionmentioning
confidence: 99%